Stochasticity and robustness analysis of microRNA-mediated ERK signaling network. (October 2018) - Zhou, Wei; Chen, Ziyi; Liu, Zhigang; Wang, Yonghua
Graphical abstract: Highlights: MicroRNAs (miRNAs) play a critical role in regulating the extracellular signal regulated kinase (ERK) pathway. The mechanisms of miRNA-mediated regulations on signal pathway require further investigation systematically. We develop a mathematical model by analyzing the precise dynamic mechanisms with miRNAs involved in the ERK pathway. Our study will provide a rich area of future research with the regulatory roles of miRNAs in cell signaling pathway. Abstract: MicroRNAs (miRNAs) play a critical role in regulating the signaling network such as the extracellular signal regulated kinase (ERK) pathway. However, the mechanisms of miRNA-mediated posttranscriptional regulations with regard to their impacts on signaling require further investigation from a systematic level. Therefore, we develop a mathematical model by analyzing the precise dynamic mechanisms with a bevy of miRNAs involved in the Ras/Raf/MEK/ERK pathway. A systems-based analysis approach is introduced into this model and the dynamics have been implemented deterministically and stochastically. Our analysis reveals that miRNAs are key participants regulating the gene expression of ERK network, and the cooperative actions of miRNAs are important in keeping the normal biological characteristics and amplification effects of the system. Meanwhile, the appearance of system disorder in the absence of miRNAs suggests that miRNAs may play a role in the pathological processes, such as tumor and inflammation. The sensitivity analysis and the kinetic parameter perturbation show that the binding of receptor (EGFR) and adaptor protein (Shc, Grb2 and Sos) under normal physiological conditions is crucial for the robustness of the whole pathway. In addition, the stochastic dynamic patterns are in a good agreement with the deterministic results, further demonstrating that the variability of the system due to the presence of some stochastic noise is low. All these will be helpful for a deeper understanding of the dynamic mechanism of miRNA-mediated ERK signal network, which might present a rich area of future research with the relevant regulatory roles of miRNAs in cell signaling pathway.